Design of an Adjustable Wind Tunnel Model - Bergfjord, Mathias; Jareteg, Adam; Lindstrand Levin, Rickard; Wallin, Lars (My University, 2012)
Wind tunnel models are used when designing race cars both as an effective way to test new ideas and a method to validate the calculations. Chalmers Formula Student (CFS) want a wind tunnel model to use in their design work and testing but making a new model for each year is restricted in time and cost. In 2011 CFS made their first wind tunnel model which was static and due to the absence of rotating wheels, had limited correlation with the real car. It could not be used by any other team since it was specific to that year’s car design. It was desirable to obtain an adjustable model with standardized interfaces to easily change the exterior design without having to remake the model. To be able to maximize the usefulness it was also important to receive numerical data from measurements to compare with calculations. This report describes the making of a reusable wind tunnel, which will decrease the time spent developing it each year and provide means of acquiring credible and desirable data. It describes the benchmarking of existing technology and what can be implemented in the project. It will also explain the design and manufacturing of the model, which problems arose and what to consider when using the resulting model or making an additional model. The goal of this project was to create a platform for CFS to use in their wind tunnel testing. This was to be done by designing and building a frame to which changeable body features would be attached. To get as realistic modelling as possible a system for having rolling wheels was designed and ways of measuring was developed. The frame and the wheels were manufactured but the body features although designed, were not manufactured and testing in the wind tunnel was outside the scope of this project. Finally some recommendations are made around the model and guidelines how to use it are drawn. This project was completed as a part of Chalmers Formula Students Advanced Research Programme to improve the aerodynamics of the car and to increase the analysis toolbox at hand. It will hopefully contribute to an increased ranking in the Formula Student contest and a gain in the international respect for Chalmers as a professional institute for education
Keywords: Teknisk mekanik; Energi; Hållbar utveckling; Strömningsmekanik och akustik; Transport; Applied Mechanics; Energy; Sustainable Development; Fluid Mechanics and Acoustics; Transport